Autopercepcion de inteligencia contextual para jugar y de competencia decisional en el futbol - Ruiz-Perez, L. M.; Navia, J. A.; Minano-Espin, J.; Garcia-Coll, V.; Palomo-Nieto, M. (Revista Internacional de Ciencias del Deporte, 2015)
The aim of this paper was to analyze decisional competence and contextual intelligence in sport among different level of expertise football players. In addition, the relationship between self-perceptions of decisional competence and contextual intelligence was assessed. Participants were 467 football players (M=20,26, DT=5,43). They were assigned three levels of expertise: Autonomic (N = 141), National (N = 253) and International (N = 73), from a group of 46 spanish clubs and several national teams. The Contextual Intelligence in Sport Questionnaire (ICD) and the Decision Making in Sport Questionnaire (CETD) were used to explore self-perceptions of players. Results showed that self-perceptions of Contextual Intelligence and Decision Making increased with the level of expertise.